Anxiety in a regular day of work: A 24 hour psychophysiological investigation in young dentists with gender comparison - Queirolo, Luca; Bacci, Christian; Roccon, Andrea; Zanette, Gastone; Mucignat, Carla (Frontiers in Psychology, 2023)
ABSTRACT Introduction and aim: Dentistry is a highly demanding profession with a strong mental and physical involvement, possibly generating anxiety. Very few studies assessed psychophysiological activity in dentists, while none tried to relate it with gender during a routine working day. This study aims at evaluating correlations between gender, psychophysiological indexes, and psychological variables. Material and methods: Data were acquired at the Dental Clinic of the University of Padua on 20 healthy young dentists (10M-10F) during a 24h period of a working day. Physiological variables (measured with E4 Empatica) were electrodermal activity (EDA), heart rate variability (HRV) and heart rate (HR). Participants anxiety was measured through a self-reported scale on patient-relationship anxiety and through the Generalized Anxiety Disorder-7 Questionnaire (GAD-7). Results: 5 (3F, 2M) participants over 20 had a GAD-7 score ≥ 10. Female gender, in comparison to Male, was associated with higher perceived patient relationship anxiety (p=0.002) and lower HRV (p adj=0.022). The gender Male, although being associated with lower level of self-reported anxiety (p=0.002), showed an equal number of subjects with a GAD-7 score ≥ 10 (p=0.371). No interaction between gender and EDA was found, nor an effect of GAD score on EDA, HRV and HR values. Higher values of EDA were found during sleep time; a difference between sleep time and working time EDA (p=0.037) and a difference between sleep time and daytime (p=0.0045). A different HR between sleep and all daytime (p<0.001) was also highlighted. Conclusion: 25% of dentists fell within generalized anxiety disorder diagnosis, compared to a maximum of 8.6% in the general population. A possible general biomarker of excessive stress response was measured: a shift of circadian sympathetic activity was found in dentists; a higher activity during sleep in comparison to working time and daytime. The Female gender was associated with higher perceived patient-approach anxiety, lower parasympathetic activity, and a comparable sympathetic activity to the Male gender, thus fostering a possible vulnerability to excessive stress. This study underlines the need to empower the psychological approach to stress and patient-relationship in dentistry.